An islamic strategy for the empowerment of muslim women in Nigeria (2013)
Several Muslim women in Nigeria lack access to sustainable and independent sources of income. The situation has no doubt contributed to household poverty within the Nigerian Muslim community. In their bid to seeking credit to engage in lawful income generating ventures, Muslim women were more often than not, compelled to patronise interest-bearing sources of finance as against their desires and the teachings of Islam. Existing studies have treated the issue of women's empowerment from eclectic angles and the challenges of Muslim Non-Governmental Organisations (NGOs) in Nigeria without suggesting an enduring and sustainable solution to the issue through an acceptable Islamic line of funding to empower female Muslims in the country. This paper, therefore, suggests the establishment of an NGO dedicated Muslim women from which Self Help Groups (SHGs) would emerge. It also suggests the establishment of Islamic Microfinance banks across the country to service the NGO and indeed its female Muslim clients. If this is done, it would go a long way in empowering the Nigerian Muslims through the means acceptable to Islam.